The Influence of Perceived Social Support and Self-Efficacy on Resilience among First Year Malaysian Students - Shreas Suresh Narayanan; Alexius Cheang Weng Onn (Kajian Malaysia, 2016)
This study sought to determine whether perceived social support and self-efficacy were significant predictors of resilience among students when the effects of other variables such as stress, age, gender, and cumulative grade point average (CGPA) were controlled for. The effect of the interaction between perceived social support and self-efficacy on resilience was also tested. The study sample consisted of 377 first year local undergraduate students from a public university in Malaysia. Multiple regression was used to analyse the data. The results indicated that both perceived social support and self-efficacy were significant predictors of resilience as higher scores on perceived social support and on self-efficacy scales predicted higher resilience. The interaction effect between these variables was also positive and significant. Further analysis using ordered probit model revealed that when a student scored higher on levels of perceived social support as well as on self-efficacy, it lowered the probability of the student being in the low resilience category and increased the probability of being in the moderately resilient and highly resilient categories. The interaction effect remained significant across all categories of resilience.